Herpes simplex virus-infected cells contain a function(s) that destabilizes both host and viral mRNAs. - Kwong, A D (1987)
The herpes simplex virus virion contains a function that mediates the shutoff of host-protein synthesis and the degradation of host mRNA. Viral mutants affected in this function (vhs mutants) have previously been derived. Cells infected with these mutants exhibit a more stable synthesis of host as well as the immediate early (alpha)-viral proteins. We now show that a function associated with purified virions of the wild-type virus reduces the half-life of host and alpha mRNAs, whereas purified vhs-1 mutant virions lack this activity. The functional half-life of many early (beta)- and late (gamma)-viral mRNAs is also prolonged in mutant virus infections. These studies suggest that the wild-type virion brings into cells a function that indiscriminately reduces the half-life of both host and viral transcripts and that the early translational shutoff of the host is a consequence of this function. This function may facilitate rapid transitions in the expression of groups of genes that are transcriptionally turned on at different times after infection.